Adding Calcium Influence on Compressive Strength of Mortar with Different Cement Variations - Khairil Yanuar; Abdul Hafizh Ihsani; Faryanto Effendi; Muhammad Suhaimi; Ruspiansyah Ruspiansyah (Journal of Business Social and Technology, 2022)
Mortar is a mixture of binder and sand in a certain ratio, the binder is cement and lime. This test aims to determine the results of the compressive strength of mortar aged 3,7,14, and 28 days on variations of cement and lime mixture. The fine aggregate used in this test is Barito Sand which is included in zone 2. With the composition of the mixture used is 1 pc : 5 ps for cement and sand, the mixture used for cement, lime and sand is 1 pc : 1_4^1kp : 5 ps. From the results of this study with the same mixture proportions, the compressive strength for the variation of cement conch (PCC) = 7.40 MPa, the variation of cement gresik (PPC) = 10.41 MPa, the variation of cement conch with a mixture of lime = 4.54 MPa and strong Press the mortar for the variation of Gresik cement with a mixture of lime = 7.90 MPa. It can be concluded that the compressive strength of mortar for cement conch with a mixture of lime is higher than the variation of cement conch, gresik and conch with a mixture of lime